Perceptions of nature of science emerging in group discussions: A comparative account of pre-service teachers from Turkey and England - Erduran, S; Kaya, E; Cilekrenkli, A; Akgun, S; Aksoz, B (Springer Verlag, 2020)
The paper presents a study about pre-service science teachers’ perceptions of the Nature of Science (NOS). Although there is a substantial amount of research on NOS in science teacher education, international comparative accounts particularly of in-depth qualitative data emerging from group discussions are fairly minimal. The primary aim of the research was to determine the changes of pre-service science teachers’ NOS perceptions following group discussions in two different national contexts: Turkey and England. Two groups of pre-service teachers from Turkey were contrasted with two groups of pre-service teachers from England. The group discussions were structured with a set of steps. In the first step, the participants were asked to reflect about NOS and record their key ideas on sticky notes. Subsequently, they were presented with a visual framework of NOS, and they were asked to situate their own ideas from the sticky notes in this image. Verbal data from group discussions were investigated by qualitative methodology using thematic analysis. The findings suggest that both groups of pre-service teachers initially focused on epistemic-cognitive aspects of NOS but their ideas became more nuanced in providing some examples about social and institutional dimensions of NOS following the introduction of the NOS image. The study contributes to the understanding of how pre-service teachers view NOS and illustrates how NOS can potentially be incorporated into group discussions in science teacher education.